Reinforcing Pediatric Nutrition Recommendations Using Low-Cost Resources to Reduce Impacts of Childhood Obesity - Wright, Allison (My University, 2023)
A statistical correlation has been made between the incidence of childhood obesity, comorbid conditions such as hypertension and diabetes, and food insecurity (Arnold et al., 2020). These studies conclude that increasing the availability of healthy food resources can combat childhood obesity and its complications (Trude et al., 2018). To increase knowledge and availability of healthy food resources, this project surveyed 212 pediatric patients for elevated body mass index (BMI) and food insecurity using the Hunger Vital Signs questionnaire on admission to the pediatric unit. Patients with elevated BMI and food insecurity were provided with nursing-led education on free and low-cost healthy food resources and family-oriented health programs. The project results concluded that 62 of 212 patients met the BMI and food insecurity criteria and only 28 of those received project education over a 12-week implementation period. Significantly fewer Spanish-speaking patients received the education, despite a higher rate of elevated BMI and food insecurity. Strategies were provided to help increase compliance with the proposed education, decreasing care gaps identified in Spanish-speaking patients who met project criteria.
Keywords: childhood obesity, food insecurity, nurse-led education, healthy food resources